IDENTIFIKASI STATUS NUTRIEN KAMBING BOERAWA DI SENTRA PRODUKSI KAMBING BOERAWA PROVINSI LAMPUNG - Yayu Suhaesti; Erwanto .; Yusuf Widodo (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The objective of this research was to find out the Boerawa goat nutrition status based on material of feed, nutritional content, and feeding management used by Boerawa goat farmers in Lampung province. There were 50 farmers to interview coming from three districts of production centers (16 farmers from Pesawaran, 17 farmers from Pringsewu, and 17 farmers from Tanggamus). This research used qualitative approach with survey method, and data were analyzed descriptively. The results showed that feed to use were merely vegetative feed (leafs). These three districts of Boerawa goat production centers have abundant potentials of agricultural resources, however these resources were not yet optimized as feed materials for farmers. Even though suffice feeding frequency was properly administered by farmers, this did not fully meet the goat necessity of vegetation feed. In addition, the nutrition content from dry material and protein from feed used by farmers showed values below standard of dry material and crude protein required by Boerawa goat. The conclusion is that the nutrition status of feed material used by farmers in Boerawa goat production centers is under nutrition.